Firm's Value Prediction Based on Profitability Ratios and Dividend Policy - Husain, T.; Sarwani; Sunardi, Nardi; Lisdawati (Finance & Economics Review, 2020)
Purpose: This study aims to empirically prove the research framework regarding the Firm’s Value based on Profitability Ratios associated with Dividend Policy. The firm's Value is measured using a Price-to-Book Value (PBV) Approach. Methods: This study included a sample of 11 firms under the automotive and components sib sector listed in the Indonesia Stock Exchange. It included data for the period of 2014-2018. This study applied path analysis using the Sobel test of the direct and indirect effects using IBM SPSS 23.0. Results: The study finds that Profitability Ratios has no significant effect on the Dividend Policy, while the Dividend Policy has no significant effect on Firm's Value too. However, the Dividend Policy does not mediate the effect of Profitability Ratios on the Firm's Value. Implications: This study could be extended further by considering all listed firms of IDX which may provide us more insights into the measurement of the financial ratios in the context of Indonesia.